Effects of specific programmed training on physical fitness, physiological and performance responses in elite judokas - Mekic, A.; Kajmovic, H.; Kapo, S.; Bajramovic, I.; Covic, N. (Homosporticus, 2018)
Aim of this research was to determine the effects of specific programmed training on morphological characteristics, motoric and functional abilities of elite judokas. Seven judo athletes (24.71±3.35 years), that have won at least one medal in the European Judo Championship or in the World or European Judo Cup during previous two years participated in study. The sub elite group consisted of 7 athletes (26.14±3.39 years) that have only won medals in national competitions (Bosnia & Herzegovina). Skin-fold (suprailiac) was significantly reduced in experimental group after the applied treatments (F = 5.38, P = 0.039). Furthermore, significant interaction effect appeared (F = 6.94, P = 0.022), which indicates significantly greater effect on the increase in volume of Right forearm in the experimental group after applied program, whereas in the control group, these values had smaller average size in the final measurement. Bench Press (F = 121.00, P = 0.000), Deep squat (F = 14.03, P = 0.003), Dead lift (F = 27.56, P = 0.000) and Hand Grip Right (F = 22.91, P = 0.000). In variables of power evaluation effects of applied treatment were also significantly better in favor of experimental group with Single high jump (F = 10.48, P=0.007), Single long jump (F = 12.79, P = 0.004) and Medicine ball toss (F = 47.25, P = 0.000). After six months of applied training protocol, regarding anthropometric measurements in experimental group of judokas, at the same time occured a reduction in the percentage of fat and suprailiac skinfold as well as an increase the of the right forearm circumference at a significant level of deduction. Furthermore, the significant increase in all variables of strength and coordination is noticable. The experimental treatment also resulted in a significant increase in aerobic and anaerobic power, as well as judo-specific fitness, whereas no significant changes were occured in flexibility variables and left-hand grip.